Perlindungan Hukum terhadap Hewan Laut Antipathes (Akar Bahar) di Kabupaten Alor, Ditinjau dari Undang- Undang No.05 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya - Efri Henderina Bail; Jimmy Pello; Rosalind Angel Fanggi (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
This study aims to find out and analyze the legal protection of marine animals in Alor Regency from Law No. 05 of 1990 concerning the Conservation of Biological Natural Resources and Their Ecosystems. The type of research used in this study uses an empirical method or called field research, which is to examine the applicable legal provisions and what happens in reality in society. The results of the discussion in this study show that, (1) the factors that cause the taking of marine animals (akar bahar) are: weak community income, weak community legal awareness factors, motive factors of perpetrators, weak supervision factors, crime scene factors (crime scenes) are difficult to detect, (2) efforts made to protect marine animals (akar bahar) are: preemptive legal protection efforts, preventive legal protection efforts, efforts to protect the law in a repressive manner.